THE FORMATION OF A UNIFIED INFORMATION ENVIRONMENT OF A BASIC UNIVERSITY - Evgeniy A. Zakharov (Высшее образование в России)
The article considers the formation of a unified information environment of a basic university. Analyzes the current state of information technology infrastructure, information scientific-educational environment of the Volgograd State Technical University and Volgograd State University of Architecture and Civil Engineering, which form the basis of the information structure of a regional basic university. The author describes the ways of integrating the information systems of the participating universities, the prospects of the development of the University site and the University portal. Special attention is paid to increasing the level of information literacy of University teachers and University staff.